(untitled) (k:ON - Kölner Online Journal für Lehrer*innenbildung, 2024)
This article presents the concept of two consecutive seminar units for student teachers of all subjects, which are intended to prepare participants for dealing with linguistically heterogeneous school classes. The first unit is designed as a language learning experience in a completely unknown language in a monolingual beginners’ class followed by a reflection phase. In the second unit, students take part in a self-experience in a bilingual subject class in English. Evaluations of the first two sessions indicate that participants developed a better understanding of multilingual learners.